Pengaruh Tindakan Closed Suction terhadap Perubahan Hemodinamik (MAP, RR, HR, SPO2) pada Pasien yang Terpasang ETT dan Ventilator di Ruang ICU - Saripatun Nisa; Rahayu Winart (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Patients with Endotracheal Tube (ETT) and mechanical ventilators often experience secretion buildup in the airway that can lead to airway obstruction, ventilation disorders, as well as changes in hemodynamic parameters. Close suction is one of the nursing interventions used to clean secretions without disconnecting the ventilator so that ventilation and oxygenation are maintained. Objective: To describe the effect of the close suction method on hemodynamics: MAP (Blood Pressure), Pulse, Respiration, and Oxygen Saturation in patients who were fitted with ETT and ventilators in the ICU room. Methods: This study used a descriptive case study design on 5 patients who were fitted with ETT and mechanical ventilators in the ICU of Santosa Bandung Kopo Hospital. Data collection was carried out by measuring hemodynamic parameters before (pretest) and after (posttest) close suction action using bedside monitor. Data were analyzed descriptively by comparing the values before and after the intervention. Results: After close suction was given, there was an increase in the mean MAP value from 87.8 mmHg to 98.8 mmHg, HR from 96.2 times/min to 101.0 times/minute, RR from 19.6 times/min to 20.0 times/minute, and SpO₂ from 99.8% to 100%. These changes show that the close suction action is able to maintain the patient's hemodynamic stability and oxygenation during the procedure. Conclusion: The close suction method has an effect on hemodynamics: MAP (Blood Pressure), Pulse, Respiration, and Oxygen Saturation in patients who are fitted with ETT and mechanical ventilators. This action can be used as a nursing intervention to help maintain the physiological stability and oxygenation of critical patients in the ICU room.